Via revistas e jornais: a seção que ecoa as polêmicas e embates em torno da educação na grande imprensa (1930-1931) - Souza, Cleber Soares De [UNIFESP] (2019)
The section “Através das Revistas e Jornais” (Flipping Through Magazines and Newspapers) is part of a pedagogical journal titled Escola Nova (New School), which was created in October 1930, by the Diretoria Geral de Instrução Pública (General Bureau for Public Education), the office which is responsible for organizing public education in São Paulo. The journal was mainly concerned with discussing, echoing, reverberating and broadcasting what the commercial press of that time published on its pages about education and society in the beginning of the said decade. It also propagated the ideals of the São Paulo Educational Society, a private entity created to think about, build upon and press forward policies by public institutions towards implementing a certain teaching system. Under the crisis and transformations in the oligarchic system and the intensification of the dispute around the State, the New School emerged as some sort of continuity, since this public agency had established a tradition in the production of pedagogical literature. From its front cover, however, the journal made clear what pedagogical trend it followed. This promoted a toughing up of the fight that the followers of Lourenço Filho, the publisher, were willing to wage. For this reason, the section “Através das Revistas e Jornais” became the object of analysis in this dissertation, whose goal was to study the controversies and clashes which resulted from a diverse array of discursive tools and devices used by the publisher in order to convince its readers of the tacit consensus he sought to establish around the political and educational project ingrained in the administrative reforms promoted by the provisional government and the Diretoria Geral de Instrução Pública. The columns of the said section reveal incongruities as to the ways to conduct an authoritarian project of society.